Uwielbiony Chrystus i życie wieczne - nadzieją Kościoła apostolskiego w świetle Listów Pasterskich - Stasiak, Sławomir (Verbum Vitae, 2006)
The Pastoral Letters in a particular way undoubtedly reflect the theology resulting from the instructions concerning Church life. In the discussed texts, we can observe a two or even a three-level understanding or the concept of he elpis - hope. On the one band, the promise of God Himself (Tt 1,2) is presented as a basis for hope, as also the person of Jesus Christ (1 Tm 1,1). On the other band, it is actually Christ w ho is the subject of Christian hope (comp. 1 Tm 1,1). This hope, however, does not limit itself to indicating its basis or subject matter. It is closely related to the saving work of God. and hecomes the essence of the life of the first Christian community - the apostolic Church (comp. Tt 2,11-13; 3,1-3).